A new frontier in understanding food: Mapping food quality to improve human and planetary health - Ahmed, Selena (2025)
Imagine a world where we truly understand what’s in our food— where everyone has access to healthy, safe, and delicious diets from sustainable food systems. Diets that not only nourish but also celebrate biodiversity and cultural traditions. This future harnesses the power of food as a vital resource for both human and planetary well-being.